2013
DOI: 10.3945/ajcn.112.046482
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at 12q24 are associated with drinking behavior in Han Chinese

Abstract: Background: Alcohol consumption is heritable, but genetic susceptibility to drinking behavior has not been investigated widely in genome-wide association studies. Objective: We aimed to identify susceptibility loci for drinking behavior (drinkers compared with nondrinkers) in Han Chinese. Design: We performed 2 genome-wide association studies including 1420 drinkers and 3590 nondrinkers in discovery, followed by a de novo replication analysis comprising 4896 drinkers and 13,293 nondrinkers. DNA samples of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
6
24
2
Order By: Relevance
“…A genome-wide association study ( GWAS ) of Japanese people found ALDH2 had the strongest association with drinking behavior (27). A similar association was also found in the Han Chinese population, with the association clustered around the ALDH2 gene location on chromosome 12q24 (28). …”
Section: Impact On Human Healthsupporting
confidence: 76%
“…A genome-wide association study ( GWAS ) of Japanese people found ALDH2 had the strongest association with drinking behavior (27). A similar association was also found in the Han Chinese population, with the association clustered around the ALDH2 gene location on chromosome 12q24 (28). …”
Section: Impact On Human Healthsupporting
confidence: 76%
“…A significant difference was noticed between our study and the study made by Ji et al That research shows that 37.4% of men and 11.6% of women were occasional binge drinkers, and just 2.9% of the young Chinese people (4.9% of men and 1.3% of women) were usual binge drinkers in 2012 [21], these results reflect, that the Chinese people's alcohol metabolizing enzymes are different [22][23][24]. The preloading is a common habit in many countries and every nation is participating at this event in different proportions.…”
Section: Discussioncontrasting
confidence: 66%
“…There is some difference compared to the data collected by Shah et al in 2009 among medical students, 14% of them do not consume alcohol [20]. Same difference (19.2%) was found in the epidemiology study among Chinese College Students in 2012 [21], but the Chinese people's alcohol-metabolizing enzymes have different genotype, they metabolize alcohol in a different pattern than other populations, so perhaps this is the cause why they consume less alcohol than other people [22][23][24].…”
Section: Discussioncontrasting
confidence: 41%
“…SNPs related to AD, maximum or average alcohol consumption, and/or frequency of consumption were selected through the NHGRI Catalog of Published Genome-Wide Association Studies (Hindorff et al 2009) and considered for AD, maximum drinks, and flushing response in the present sample of males. Two previous case-control GWAS of alcohol consumption (“drinkers” vs. “non-drinkers”) have been performed in Chinese or Japanese populations, each identifying an additional SNP associated with drinking behavior within 1MB of ALDH2 - rs10774610 in CCDC63 (Takeuchi et al 2011) and rs11066280 near C12orf51 (Yang et al 2013). In both papers, the authors note a lack of independence between these SNPs and rs671.…”
Section: Resultsmentioning
confidence: 99%